Comparative Effects Of A Four-Week Mountaineering Training Program On Red Blood Cell Count At Medium And High Altitudes (Journal of Pharmaceutical Negative Results, 2024)
This study investigated the influence of a four-week mountaineering training program on red blood cell (RBC) count among selected trainees at two different altitudes: medium altitude (2050 m) and high altitude (2700 m). Twenty trainees from Himachal Pradesh of the age group 18-25 years, were selected, and exposed to four-week training at two different high altitude training centres namely; Atal Bihari Vajpayee Institute of Mountaineering and Allied sports, Manali (2050 m) and Atal Bihari Vajpayee Institute of Mountaineering and Allied sports, Narkanda (2700 m) in Himachal Pradesh. These trainees were divided equally into two groups and assessed at three intervals i.e. pre-test (Day 0), mid-test (Day 14), and post-test (Day 28). Descriptive statistics, repeated measures ANOVA, and trend analyses were employed to examine within-subject and between-group differences. The results revealed no statistically significant changes in RBC counts over time or between altitude groups. Linear and quadratic trends were also found to be non-significant. These findings suggest that altitude-related physiological adaptations in RBC count may require longer training durations or more extreme environmental stimuli. Future research should explore longer-duration interventions and include additional haematological markers.